Formulation Study for Enteric Microspheres of Tenoxicam Using Cellulose Acetate Phthalate Part-II: Modulation of Ulcerogenic Effect¦ - OZLEN SAHIN, NEFISE; ARSLAN, HAKAN (Asian Journal of Chemistry, 2010)
One of the most significant adverse effects of oral dosage forms is their gastric irritancy. This problem can be solved by enteric coating. In this project, cellulose acetate phthalate, a polymer usually utilized for gastrointestinal film coating of tablets, was used to prepare enteric microspheres. Tenoxicam, an antiinflammatory drug causing irritation on stomach mucosa on oral administration, was selected as a model drug. Cellulose acetate phthalate microspheres of tenoxicam were prepared with solvent evaporation technique. After preformulation studies with differential thermal analysis and thermal gravimetry in the first part of this project, in vitro dissolution studies and in vivo investigations testing the gastric irritancy and antiinflammatory effect of microspheres were carried out in this part. Data indicate that enteric microspheres reduced the gastric irritancy of the pure drug. Microsphere formulation didn't influence the therapeutic efficacy (antiinflammatory activity) of tenoxicam. The data obtained from in vitro dissolution studies revealed the controlled release behaviour of tenoxicam from the microspheres in intestinal medium. Consequently, cellulose acetate phthalate is an appropriate polymer for preparation of enteric microspheres of tenoxicam.